2022
DOI: 10.1007/s11686-022-00530-8
|View full text |Cite
|
Sign up to set email alerts
|

Acaricidal Efficacy of Biosynthesized Zinc Oxide Nanoparticles Against Hyalomma dromedarii (Acari: Ixodidae) and Their Toxic Effects on Swiss Albino Mice

Abstract: Purpose The current study aimed to investigate the efficacy of zinc oxide nanoparticles (ZnO NPs) synthesized by Melia azedarach aqueous extract to control Hyalomma dromedarii tick, and to evaluate their toxic effects on Swiss albino mice. Methods ZnO NPs were synthesized using M. azedarach aqueous extract. UV–visible spectroscopy, Fourier transform infrared spectroscopy, scanning electron microscopy, and energy-dispersive spectroscopy were used to charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…The nanomaterials developed by a biological route had shown relatively lower LC 50 compared with nanomaterials synthesized following chemical routes. This is evident from the study by Abdel-Ghany and co-workers, who reported an LC 50 of 11.6 mg/mL in the egg immersion test compared with the lower (1.8) seen in our study [ 42 ]. In contrast to that, in our previous study, the LC 50 attributed to the green-mediated ZnO nanoparticles of neem and lemon grass were lower for adults (4.76 and 4.92 mg/L, respectively) compared with LC 50 of 5.03 mg/L in adults used for current study [ 43 ].…”
Section: Discussionsupporting
confidence: 64%
“…The nanomaterials developed by a biological route had shown relatively lower LC 50 compared with nanomaterials synthesized following chemical routes. This is evident from the study by Abdel-Ghany and co-workers, who reported an LC 50 of 11.6 mg/mL in the egg immersion test compared with the lower (1.8) seen in our study [ 42 ]. In contrast to that, in our previous study, the LC 50 attributed to the green-mediated ZnO nanoparticles of neem and lemon grass were lower for adults (4.76 and 4.92 mg/L, respectively) compared with LC 50 of 5.03 mg/L in adults used for current study [ 43 ].…”
Section: Discussionsupporting
confidence: 64%
“…Up to seven days of incubation, daily data on the death rate was kept. Daily observations were conducted using appropriate changes to previously published procedures, and after the mortality rate reached 50%, the adult tick mortality (%) was recorded [ 53 , 64 ].…”
Section: Methodsmentioning
confidence: 99%
“…Ag-NPs Antiparasitic Inhibited larvae of malaria vector, Anopheles subpictus Grassi [53] Ag-NPs Antiparasitic inhibited the growth and metabolic activity of promastigotes, hence preventing Leishmania tropica and its antileishmanial effects. [54] Ag-NPs Antiparasitic Showed antiplasmodial activity against P. falciparum.…”
Section: This Workmentioning
confidence: 99%
“…Adult immersion test was used in the bioassay of R. chalepensis essential oil (REO) against R. annulatus ticks according to Abdel-Ghany et al [43]. Five different concentrations (10, 5, 2.5, 1.25, and 0.625%) of REO were prepared in 70% ethyl alcohol.…”
Section: Acaricidal Activity Of the Essential Oilmentioning
confidence: 99%